Kelayakan Finansial Proyek Investasi Pengebunan Jambu Biji Kristal Secara Monokultur di Wilayah Kabupaten Banyuwangi - Agus Supriono; Rining Kasih Widyastuti; Cindera Rosa Damascena; Rena Yunita Rahman; Ratih Apri Utami; Rachmad Udhi Prabowo (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
Crystal guava has a promising market potential due to its relatively high demand, especially in various supermarkets—both in small towns and major cities across Indonesia—and its selling price is relatively stable. Crystal guava has several advantages compared to other guava varieties, including a fresher and sweeter taste, a crunchy texture, thick flesh, and being almost seedless. It is relatively easy to cultivate, has a high harvesting frequency, and tends to bear fruit throughout the year regardless of the season. Therefore, farmers in Karanggondo Village, Tegalsari District, Banyuwangi Regency, have begun cultivating it as a monoculture crop since 2012. Considering this situation, it is deemed interesting to conduct research on the financial feasibility of a Crystal guava plantation investment project under a monoculture system per hectare in Banyuwangi Regency. The research results show that the investment project is financially “feasible.” However, if production volume and product price decrease by up to 48.96%, and variable operating costs increase by up to 79.02%, while other factors remain constant, the Crystal guava monoculture plantation investment project per hectare in Banyuwangi Regency becomes financially “unfeasible.” Among these factors, the decline in production volume and selling price are found to be relatively “more sensitive” in influencing the project’s financial feasibility.